Glück in the narratives of Jörg Wickram - Politis, Cordula (Trinity College (Dublin, Ireland). Department of Germanic Studies, 2001)
In this thesis I want to consider the concept of glück, the German equivalent of Fortuna, in the narratives of the sixteenth century author Jörg Wickram. I will focus on two major themes in Wickram's representation of glück. First, I will consider the occurrence of glück in relation to another major force, God. Second, I will consider two types of glück that we may distinguish in the narratives, one operating externally and the other operating internally, the former affecting characters from without, the latter originating more in their own actions. My aim is to define the impact which glück has on the lives of the characters, and the extent to which the characters may in turn influence glück. My approach is twofold: I begin the exploration of each theme by close textual analysis of the narratives; the findings of the textual analysis are then related to a historical background. This background is constituted by various sources, both medieval and early modern, that dwell on the nature of glück, or Fortuna. The medieval aspect is represented by the views of Boethius, whose account of Fortuna may be regarded as formative for the Middle Ages. Boethius' scepticism stands in contrast to certain exponents of Renaissance thought, such as Petrarch, Poggio Bracciolino and Enea Silvio Piccolomini. The latters' emphasis on human control over Fortuna differs markedly from the pessimism advocated by Sebastian Brant and Hans Sachs. By evaluating Wickram's glück against the background of these diverse accounts, I will determine his position in a wider historical context.
Keywords: Germanic Studies, Ph.D.; Ph.D. Trinity College Dublin